Reorientation of Environmental Criminal Law Enforcement through the Formulation of Corporate Community Service Orders - Ainun Jiwanti (Dinasti Research, 2025)
The importance of legal protection for the environment in Indonesia is a critical issue, as judicial decisions in environmental crime cases often fail to consider the environmental damage caused by offenders. This study identifies a research gap in the legal approach, which predominantly focuses on protecting human rights to a healthy environment while neglecting the inherent rights of the environment itself. The objective of this study is to explore the role of law in positioning the environment as a subject that deserves protection in environmental crime cases. Utilizing doctrinal legal research methodology, which examines law based on established doctrines, the study finds that environmental destruction is primarily viewed as a violation of human rights rather than a violation of the environment's own rights. The key findings suggest the necessity of a new formulation in environmental criminal law enforcement, one that is environmentally oriented. One such idea proposed is the